The Building of Cities : Development and Conflict - Kaiser, Harvey H., 1936- (Book collections on Project MUSE., 1978)
In this classic book that records a moment in the history of urban planning, the architect and city planner Harvey H. Kaiser examines the city-building process from the time when a proposal for urban development is first conceived to the early stages of construction. To illuminate the factors that underlie acceptance or rejection of community development, Kaiser focuses on the proposals for three towns in upstate New York-Lysander (near Syracuse) and Gananda and Riverton (both near Rochester). These were brand-new developments and municipalities, and thus quite different from other trends of suburbanization that attached development onto existing municipalities. Step by step, he describes what happened in each of these communities during the presentation of the initial proposal, how parties interacted with each other, and how the climate of the community influenced the actions of the parties. Basing his work on hundreds of interviews, attendance at public meetings, and a review of many articles and documents, Kaiser shows that in each case the emergence of controversy and degree of acceptance was influenced by the developer's leadership, the characteristics of the developer's organization, and the method of presenting the proposal to the public. Kaiser brings to his comparative approach a background in the rough and tumble of day-to-day project management and the development of plans as well as their administration. First published in 1978, The Building of Cities remains an invaluable resource for developers, architects, public officials, and citizens involved in local government.